Effects of GLP-1 agonists and SGLT2 inhibitors during pregnancy and lactation on offspring outcomes: a systematic review of the evidence - Muller, Dion R. P.; Stenvers, Dirk J.; Malekzadeh, Arjan; Holleman, Frederik; Painter, Rebecca C.; Siegelaar, Sarah E. (Frontiers in Endocrinology, 2023)
Abstract Aims/hypothesis Glucagon-like peptide 1 (GLP-1) agonists and sodium-glucose co-transporter-2 (SGLT2) inhibitors are novel drugs which have recently seen rapid uptake in the treatment of type 2 diabetes and obesity. The aim of the present study was to systematically review all available data on the offspring effects of GLP-1 agonists and SGLT2 inhibitors during pregnancy and lactation. Methods PubMed, clinicaltrials.gov, FDA and EMA product information were searched on GLP-1 agonists and SGLT2 inhibitors in pregnancy and lactation from inception up to 19 April 2022. We approached both the Netherlands Pharmacovigilance Centre Lareb and the Teratology Information Service (TIS) of Switzerland. Eligible studies investigating the safety (including congenital anomalies, fetal growth) in animals or humans, or reporting the degree of transfer of these drugs to the fetus, breast milk or breastfed neonate. Results 42 records. In animal studies, GLP1-agonists were associated with reduced fetal weight and/or growth, delayed ossification and skeletal variants. Exendin-4 (GLP1-agonist) was not transported across the maternal-fetal placental interface. In human studies, exenatide (GLP1-agonist) showed a fetal-to-maternal peptide concentration ratio of ≤ 0.017 in ex vivo human placental perfusion. Liraglutide (GLP1-agonist) showed no significant maternal to fetal transfer in a human study. In animal studies, GLP-1 agonists were excreted in breast milk; human data on excretion were not available. In animal studies, SGLT2 inhibitors were generally safe during the first trimester but exposure during the period coinciding with the late second and third trimester of human renal development, caused dilatation of the renal pelvis and tubules in rats. Human data consisted of a pharmaceutical database of inadvertent pregnancies during SGLT2 inhibitor use, which found an increase in miscarriages and congenital malformations. In animal studies SGLT2 inhibitors were excreted in breast milk and affected neonatal growth, but human data are not available. Conclusions/interpretation Although our findings may suggest limited placental passage of GLP-1 agonists, we found evidence for adverse offspring effects of GLP-1 agonists and SGLT2 inhibitors also in human studies. Our findings broadly support the advice to discontinue GLP-1 agonists and SGLT2 inhibitors during pregnancy and lactation.